SISTEM PELAYANAN ADMINISTRASI DESA BABAKANLOR BERBASIS DIGITAL (SIBAKLOR) DIGITAL-BASED BABAKANLOR VILLAGE ADMINISTRATION SERVICE SYSTEM (SIBAKLOR) - Rumanama, Abdul Ashari; Muhyi, Muhammad Ali; Arief, Annissa Fitriah; Muslim, Ahmad Buchori; Kusuma, Jaka Wijaya; Sulaeman, Yeni (LPPM Universitas Bina Bangsa, 2024)
The Babakanglor village service system faces significant challenges, especially in relation to limited resources, technical and infrastructure. The implementation of a digital-based village service system aims to increase efficiency, transparency and quality of public services in Babanganlor village. Through the PTMGRMD Banten 2024 activities various problems can be identified, including the lack of skills of village service staff in managing digital technology. The survey shows that although there are obstacles, implementation strategies can focus on technical training and understanding for village staff to be able to manage the service system well. Apart from that, there needs to be monitoring efforts so that the village service system (SIBAKLOR) can support the sustainability of this program. The training and mentoring methods that have been carried out show that the digital-based service system (SIBAKLOR) implemented by the Babakanlor Village government is more efficient, saves time, accesses information such as making business permits, making disability certificates (SKTM), covering letters for making KTPs., and other information is obtained easily and accurately, and with data management that was previously manual-based, it has become digital-based.